2006
DOI: 10.1002/chin.200606273
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Cobalt Catalysts for the Synthesis of Hydrocarbons from CO and H2

Abstract: Organic chemistry Z 0200 Bimetallic Cobalt Catalysts for the Synthesis of Hydrocarbons from CO and H 2 -[75 refs.]. -(LAPIDUS, A. L.; TSAPKINA, M. V.; KRYLOVA, A. Y.; TONKONOGOV, B. P.; Russ. Chem. Rev. (Engl. Transl.) 74 (2005) 6, 577-586; Zelinsky Inst. Org. Chem., Russ. Acad. Sci., Moscow 117913, Russia; Eng.) -Lindner 06-273

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Promoters such as Pd, Pt, Re, and Ru are added to the Co catalysts to facilitate better reduction of Co as it has strong interaction with Al 2 O 3 than other supports [12,13]. It is reported by many researchers that Pd promoter enhances adsorption sites for H 2 on Co catalyst and thus increasing the hydrogenation rate in FT synthesis [14][15][16]. Guczi et al [17] showed that Pd as a promoter to Co/SiO 2 increased the relative fraction of alkanes in FT synthesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Promoters such as Pd, Pt, Re, and Ru are added to the Co catalysts to facilitate better reduction of Co as it has strong interaction with Al 2 O 3 than other supports [12,13]. It is reported by many researchers that Pd promoter enhances adsorption sites for H 2 on Co catalyst and thus increasing the hydrogenation rate in FT synthesis [14][15][16]. Guczi et al [17] showed that Pd as a promoter to Co/SiO 2 increased the relative fraction of alkanes in FT synthesis reaction.…”
Section: Introductionmentioning
confidence: 99%